Vpliv načina sporazumevanja na kakovost življenja pri bolnikih po odstranitvi grla - Boltežar, Gašper (Zdravniški vestnik, 2007)
Laryngectomy is the most successful mode of treating an advanced laryngeal andhypopharyngeal cancer: It results in the loss of ability of speech communication. In Slovenia the two most common ways of voice rehabilitation after laryngectomy are esophageal speech (ESA and tracheoesophageal speech (TES). The aim of the study was to compare the influence of these two communication modes on patients' quality of life and to determine the factors influencing the choice of communication mode after laryngectomy. There were 22patients communicating with TES and 3 Z communicating with ES included in the study. A standardized questionnaire about quality of life (Voice-Related Quality of Life) was used to compare both groups. The patients also assessed their new way of communication on visual analogue scale, and how it affects their lives in general. The data on patients' characteristics, their place of living, mode of treatment, treatment complications, and possible swallowing problems were obtained from the medical documentation. The two groups did not differ with regard to the factors possibly influencing the choice of communication mode. The results of the questionnaire did not show any significant differences between the patients with ES and the patients with TES. The patients with TES stated significantly smaller deterioration of the quality of their lives after laryngectomy than the patients with ES. The patients with TES had fewer problems with the communication in the noise and with social life than the patients with ES but the differences were not significant. The best way of speech rehabilitation after laryngectomy would bethe insertion of tracheoesophageal prosthesis and simultaneous teaching of ES. Thus the patient gets the possibility for verbal communication soon after the operation and also learns the mode of communication without any devices. Both modes of speech rehabilitation enable good quality of life after laryngectomy.
Keywords: ezofagealni govor; Glas, kvaliteta; govor; Govor iz požiralnika; grlo; Grlo, novotvorbe; Kvaliteta življenja; Laringektomija; Laryngeal Neoplasms; Laryngectomy; Quality Of Life; Speech, Esophageal; sporazumevanje; Surgery; Voice Quality